Hak Guna Bangunan di atas Tanah Wakaf sebagai Terobosan Baru Pemberdayaan Tanah Wakaf Secara Produktif - Fahrul Fauzi; Lutfi Djoko Djumeno (Badan Wakaf Indonesia, 2021)
The purpose of this research is to provide an idea of how to realize the potential application of the concept of granting the right to build on waqf land. This concept is a new thing that can add value to waqf land so that it can be optimized productively without losing the basic essence of waqf itself. The research method used in writing this article is normative legal research. Using primary legal materials in the form of legislation on waqf and land rights, as well as secondary legal materials in the form of scientific articles related to waqf and land rights. The data analysis technique used in organizing the available data is a qualitative data analysis technique. This study found that waqf land has similarities in practice and concept to the right of management. So, if land managed properly can be granted the right to build, Waqf land can also be granted the right to build. The benefits of implementing this concept in the future could be felt by developers, nazhir, and the general public. Developers get benefits in the form of freedom from land acquisition costs and can guarantee the right to build on waqf land. Nazhir gets benefits in the form of land use fees and recommendation fees that must be paid by the developer as a condition for using waqf land and for certification purposes. Then the profits received by Nazhir can be used for the welfare of the people according to the waqf pledge.